miR-23a regulation of X-linked inhibitor of apoptosis (XIAP) contributes to sex differences in the response to cerebral ischemia - Siegel, Chad (National Academy of Sciences, 2011)
It is increasingly recognized that the mechanisms underlying ischemic cell death are sexually dimorphic. Stroke-induced cell death in males is initiated by the mitochondrial release of apoptosis-inducing factor, resulting in caspase-independent cell death. In contrast, ischemic cell death in females is primarily triggered by mitochondrial cytochrome c release with subsequent caspase activation. Because X-linked inhibitor of apoptosis (XIAP) is the primary endogenous inhibitor of caspases, its regulation may play a unique role in the response to injury in females. XIAP mRNA levels were higher in females at baseline. Stroke induced a significant decrease in XIAP mRNA in females, whereas no changes were seen in the male brain. However, XIAP protein levels were decreased in both sexes after stroke. MicroRNAs (miRNAs) predominantly induce translational repression and are emerging as a major regulators of mRNA and subsequent protein expression after ischemia. The miRNA miR-23a was predicted to bind XIAP mRNA. miR-23a directly bound the 3′ UTR of XIAP, and miR-23a inhibition led to an increase in XIAP mRNA in vitro, demonstrating that XIAP is a previously uncharacterized target for miR-23a. miR-23a levels differed in male and female ischemic brains, providing evidence for sex-specific miRNA expression in stroke. Embelin, a small-molecule inhibitor of XIAP, decreased the interaction between XIAP and caspase-3 and led to enhanced caspase activity. Embelin treatment significantly exacerbated stroke-induced injury in females but had no effect in males, demonstrating that XIAP is an important mediator of sex-specific responses after stroke.